Long-term multicomponent exercise enhances functional mobility in early-stage Parkinson’s disease: a 48-month retrospective cohort study - Moura, Marcos; Ferreira, Marina Lívia Venturini; Speri, Filipe Duo; Alves, Lucas Celsius Matos; Rostirola, João Vitor Cerávolo; de Campos, Edevaldo Donizetti; Conceição, Miguel S. (Frontiers in Physiology, 2025)
BackgroundLong-term effects of structured exercise on functional capacity in Parkinson’s disease (PD) remain poorly understood.ObjectiveTo investigate the impact of a 48-month multicomponent exercise program on mobility, aerobic capacity, and muscle mass in individuals with early-stage PD, and to examine baseline predictors of functional performance.MethodsThirty-three patients with PD (Hoehn & Yahr stages 1–2) participated in a supervised, thrice-weekly program including aerobic, resistance, balance, and flexibility exercises. Assessments at baseline and 48 months included the Timed Up and Go (TUG), Six-Minute Walk Test (6MWT), peak oxygen uptake (VO2peak), and muscle mass. Minimal detectable change (MDC), effect sizes, and linear regressions were computed.ResultsAfter 48 months, TUG time decreased by −3.8 s (95% CI: −5.0 to −2.6; p < 0.001; dz = −1.12) and 6MWT distance increased by +88.8 m (95% CI: 45.1 to 133.0; p < 0.001; dz = 0.72), both exceeding MDC thresholds. VO2peak (−1.1 mL·kg−1·min−1; p = 0.142) and muscle mass (−0.7 kg; p = 0.068) showed no significant changes. VO2peak was the sole independent predictor of functional performance at baseline and follow-up, while muscle mass had limited explanatory value. Improvements were observed in both disease stages, with similar effect sizes.ConclusionLong-term engagement in a multicomponent exercise program produces sustained functional improvements exceeding measurement error in mobility among individuals with early-stage PD, independent of changes in aerobic capacity or muscle mass. VO2peak consistently predicted functional outcomes, highlighting aerobic fitness as a key therapeutic target. These findings support the systematic integration of structured, multicomponent exercise into standard care protocols to preserve mobility and independence in PD.